GC Content of Early Metazoan Genes and Its Impact on Gene Expression Levels in Mammalian Cell Lines. (21st February 2018) - Gul, Ismail Sahin; Staal, Jens; Hulpiau, Paco; De Keuckelaere, Evi; Kamm, Kai; Deroo, Tom; Sanders, Ellen; Staes, Katrien; Driege, Yasmine; Saeys, Yvan; Beyaert, Rudi; Technau, Ulrich; et al.
Abstract: With the genomes available for many animal clades, including the early-branching metazoans, one can readily study the functional conservation of genes across a diversity of animal lineages. Ectopic expression of an animal protein in, for instance, a mammalian cell line is a generally used strategy in structure–function analysis. However, this might turn out to be problematic in case of distantly related species. Here we analyzed the GC content of the coding sequences of basal animals and show its impact on gene expression levels in human cell lines, and, importantly, how this expression efficiency can be improved. Optimization of the GC3 content in the coding sequences of cadherin, alpha-catenin, and paracaspase of Trichoplax adhaerens dramatically increased the expression of these basal animal genes in human cell lines.